EKSISTENSI RADIO REPUBLIK INDONESIA KENDARI PADA ZAMAN NOW - Abdul Jalil (UIN Siber Syekh Nurjati Cirebon, 2018)
Radio Republik Indonesia or RRI along with the development of globalization is required to be more creative, especially in greeting fans. Generation No w certainly harder to contribute unless introduced early on, in addition to the media for now more accessible, would need an innovation in order to remain one of the media that can entertain and provide information. The author has since been involved as one of the broadcasters of Rentak Pelangi Bumi Anoa (RPBA) Javanese language in 2017 to see that all this time (before 2018), RRI Kendari is still C type with RPBA program only able to accommodate most of ethnic living in Anoa earth, Makassar , Bugis, Bajo, Tolaki, Buton, Muna, Moronene, Sunda, and Java, while some other ethnic groups have not been involved due to space constraints, such as Toraja and Bali, but since early 2018 has changed to type B. With type change, RPBA is no longer used, but merged into program 4 that is art and culture. This paper aims to reveal the need for the use of regional languages for the present generation to continue to love and uphold the noble values of Muna culture in particular, and generally on the audience to understand the culture of each region. In addition, this paper is the result of multicultural practice practice on RRI Kendari, with focus on Muna language RPBA. The method used is descriptive analytics that describe broadcast RPBA Muna language from the opening segment to greet with fans RRI Muna language, after it was analyzed. The results of this paper show that the overall contents of the song or hello poet with fans was more because the network, utamanay when the choice of the song is still not in the cluster.